The Role of the ASEAN Maritime Forum in Addressing the Complexity of Illegal Fishing in the Strait of Malacca - Chalila Putri Komara; Windy Dermawan (Faculty of Social and Political Sciences University of Bangka Belitung, 2025)
The Strait of Malacca, one of the world’s busiest maritime routes, faces persistent threats from Illegal, Unreported, and Unregulated (IUU) fishing, which undermines marine resource sustainability, economic security, and regional stability. This study analyzes the role of the ASEAN Maritime Forum (AMF) in addressing IUU fishing through the lens of international cooperation and maritime security theories. Employing a qualitative descriptive-analytical approach and case study method, the research draws on secondary data from ASEAN documents, national regulations, international reports, and scholarly sources. Findings show that the AMF functions as a regional dialogue and coordination platform, facilitating intelligence sharing, joint patrols, capacity building, and policy harmonization among ASEAN member states. Notable mechanisms include the ASEAN Monitoring, Control, and Surveillance (MCS) network, Malacca Straits Patrols, and the ASEAN Regional Plan of Action to Combat IUU Fishing. While these initiatives have contributed to improved maritime domain awareness and reduced incidents by up to 20% in recent years, the AMF’s operational impact remains constrained by disparities in technical capacity, sovereignty sensitivities, limited enforcement authority, and funding shortages. The study concludes that strengthening AMF effectiveness requires harmonizing fisheries laws, enhancing technological integration, ensuring sustainable financing, and fostering cross-sector collaboration with external partners. Ultimately, the AMF holds strategic potential as a pillar of collective maritime governance in Southeast Asia, yet its success hinges on transforming political consensus into binding, coordinated, and enforceable actions.